2012
DOI: 10.1371/journal.pone.0048182
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Youth Locomotion Ground Reaction Forces Using an Accelerometer-Based Activity Monitor

Abstract: To address a variety of questions pertaining to the interactions between physical activity, musculoskeletal loading and musculoskeletal health/injury/adaptation, simple methods are needed to quantify, outside a laboratory setting, the forces acting on the human body during daily activities. The purpose of this study was to develop a statistically based model to estimate peak vertical ground reaction force (pVGRF) during youth gait. 20 girls (10.9±0.9 years) and 15 boys (12.5±0.6 years) wore a Biotrainer AM ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 26 publications
10
70
1
Order By: Relevance
“…As previous studies have demonstrated positive correlations peak vertical and resultant GRF and LR with waist, thigh, and tibia accelerations 47 and the ankle is closest in location to ground contact, we hypothesized that ankle accelerations would have higher positive correlations than waist, thigh, or tibia accelerations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous studies have demonstrated positive correlations peak vertical and resultant GRF and LR with waist, thigh, and tibia accelerations 47 and the ankle is closest in location to ground contact, we hypothesized that ankle accelerations would have higher positive correlations than waist, thigh, or tibia accelerations.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have shown positive correlations of peak accelerations, measured with body-worn accelerometers, with peak vertical and resultant GRF and LR in both adults 46 and children. 7 However, these studies used accelerometers placed on the hip, thigh, tibia, and/or wrist but did not investigate the relationship of ankle accelerations with peak GRF and LR. Since peak LR is a key indicator of loading underfoot 8 and the ankle is closer in location to ground contact, ankle peak accelerations may provide higher correlations with peak GRF and LR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Lo et al [109] and Neugebauer et al [117] propose to further simplify kinetic analysis using micro-inertial sensors for GRF measurement. Although GRF is critically important for kinetics analysis, it can only be used to infer virtual force generated at each joint by inverse dynamics, which may not be enough in practice.…”
Section: A Wearable Sensorsmentioning
confidence: 99%
“…A relatively high sensitivity and specificity of 88% and 83%, respectively, were achieved for detecting pressure transitions, and a specificity of 77% was achieved for detecting medial and lateral contact. Similarly, Neugebauer et al [117] used a waist-worn accelerometer to estimate GRF. A mixed effect and generalised regression model, which is not subject specific, is used to predict the peak vertical GRF from the waist-worn sensor.…”
Section: ) Pressure Insole Grf Estimationmentioning
confidence: 99%